Ice speed of a Greenlandic tidewater glacier modulated by tide, melt, and rain - S. Sugiyama; S. Sugiyama; S. Tsutaki; S. Tsutaki; D. Sakakibara; D. Sakakibara; I. Asaji; K. Kondo; Y. Wang; E. Podolskiy; G. Jouvet; G. Jouvet; et al. (The Cryosphere)
Ice discharge from the Greenland ice sheet is controlled by tidewater glacier flow speed, which shows large variations on different timescales. Short-term speed variations are key to understanding the physical processes controlling glacial motion, but studies on Greenlandic tidewater glaciers, particularly near the calving front, are sparse. Here, we present high-frequency ice speed measurements performed at 0.5–4 km from the front of Bowdoin Glacier, a tidewater glacier in northwestern Greenland. Three global positioning system (GPS) receivers were operated for several weeks in July of 2013–2017 and 2019. Horizontal ice speed varied over timescales of hours to days, including short-term speed-up events as well as diurnal and semidiurnal variations. Frequency analysis revealed that semidiurnal signals decay upglacier, whereas diurnal signals are consistently observed over the study area. Speed-up events were associated with heavy rain, and longer-term variations were correlated with air temperature. Uplift of the glacier surface was observed during fast-flowing periods, suggesting basal separation due to elevated water pressure. These observations confirm the strong and immediate impact of meltwater and rainwater on subglacial water pressure and sliding speed. Tidally modulated ice speed peaks coincided with or slightly before low tide, which demonstrates the key role viscoelastic ice dynamics play in response to changing hydrostatic pressure acting on the glacier front. Our study results reveal details of short-term flow variations near the front of a Greenlandic tidewater glacier and provide insights into calving glacier dynamics. During the melt season, ice speed is controlled by atmospheric conditions through meltwater production and rain events, as is commonly observed in alpine glaciers, but additional complexity arises from tidal influence near the calving front.